MarBel Math: Android-Based Electronic Mathematics Book to Enhance Learning Outcomes for Fourth-Grade Students - Dzulfiqar, Miqdad; Bektiningsih, Kurniana (International Journal of Elementary Education, 2024)
The limitations in providing innovative learning media that align with the developments in Science and Technology negatively impact students, such as difficulty understanding the material, low learning motivation, and poor learning outcomes. This research aims to develop an Android-based electronic book learning media named MarBel Math for flat shapes material in the fourth grade of Elementary School. This research employs the Research and Development (R&D) method with the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques utilize both test and non-test methods. The data analysis technique involves both quantitative and qualitative data analysis methods. The validation results from content experts yielded an average score of 92%, classified as "very suitable," In the validation test by media experts, an average score of 85% was obtained, classified as "suitable". The study utilized t-test and n-gain analysis to assess the effectiveness of implementing MarBel Math learning media. This test revealed an average increase in student learning outcomes by 68%, with the average increasing from the initial or pre-test score of 54 to 85 in the post-test. From these results, MarBel Math learning media is considered to have very suitable qualifications for use in learning activities and is quite effective in improving student learning outcomes, especially in mathematics learning for flat shapes material in fourth-grade Elementary School.